The practice of building control in relation to illegal building / Norhafizah Hassan - Hassan, Norhafizah (Faculty of Architecture, Planning and Surveying, 2008)
In Malaysia the issue of illegal building is not a new issue. The problems of illegal building can give effect to the local authority, neighbour, occupant and public surroundings. However for the local authority they also prepared some explanation and information to the public before their doing the plan approval according current regulations. But nowadays the owner of building still not followed the explanation and information that local authorities have been prepared. For them, there have their own reason why they do this construction without getting formal permission from the local authority. The objectives of this research are to identify the building control aspect in respect of building regulation for building approval, to identify the common type of illegal building or structure that happen in building construction and to analyse the enforcement practice and action made by a local authority in controlling illegal building. In complete these researches the questionnaire have been prepared. The questionnaire has answers by the staff of local authority from Building Control Department. From the analysis the conclusion is the local authority has their own action enforcement in settle the problems of illegal building. But the public also should have responsibilities to make sure they followed the regulation from local authority.